Sosialisasi dan Bimbingan Teknis Indeks Pembangunan Olahraga (IPO) di Wilayah Kota Tangerang Tahun 2024 - Iman Kurniasandi; Septian Williyanto; Kaonang Kaonang; Irmansyah Wahyudin (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2025)
In general, the definition of sport is a person's physical and psychological activity which aims to maintain and improve the quality of health. Sport is very important for human life. The reason is, regular exercise has a positive impact on physical development. Not only does it have a positive impact on a person's physical development, but it also has an impact on their mental development. This effect increases the efficiency of the body's organs, normalizes blood circulation, breathing and digestion. One of the efforts to find out how much public awareness there is about sports is that the Tangerang City Government, through the Youth and Sports Department, is carrying out a derivative program from the Ministry of Youth and Sports, namely socializing the Sports Development Index related to where this program can be a benchmark for how fit the people of Tangerang City are. The implementation will be held on November 21 2024, which will coincide in the Cisadane Building Hall, Tangerang City.